2006
DOI: 10.1348/014466505x29134
|View full text |Cite
|
Sign up to set email alerts
|

A factor analysis of the Wechsler Adult Intelligence Scale 3rd Edition (WAIS‐III) in a low IQ sample

Abstract: This study does not support the four-factor solution which underlies WAIS-III index scores in a low IQ population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…The Spatial Span test from the Wechsler Memory Scale-3rd Edition (WMS-III; Wechsler, 1997b), which loaded on a working memory factor when not allowed to split between factors, loaded more strongly on the perceptual factor than it did on a working memory factor when split loadings were permitted. In studies of special clinical populations examining only WAIS-III subtests, factor analysis confirmed that nonverbal subtests, Picture Completion, Block Design, and Matrix Reasoning all loaded on the same factor (Jones et al, 2006;Ryan & Paolo, 2001;van der Heijden & Donders, 2003). These studies all support the hypothesis that the nonverbal subtests measure a single perceptual construct.…”
Section: Unravelling Nonverbal Cognitive Performance In Acquired Aphasiamentioning
confidence: 59%
See 1 more Smart Citation
“…The Spatial Span test from the Wechsler Memory Scale-3rd Edition (WMS-III; Wechsler, 1997b), which loaded on a working memory factor when not allowed to split between factors, loaded more strongly on the perceptual factor than it did on a working memory factor when split loadings were permitted. In studies of special clinical populations examining only WAIS-III subtests, factor analysis confirmed that nonverbal subtests, Picture Completion, Block Design, and Matrix Reasoning all loaded on the same factor (Jones et al, 2006;Ryan & Paolo, 2001;van der Heijden & Donders, 2003). These studies all support the hypothesis that the nonverbal subtests measure a single perceptual construct.…”
Section: Unravelling Nonverbal Cognitive Performance In Acquired Aphasiamentioning
confidence: 59%
“…Directly treating non-linguistic cognitive abilities in people with aphasia may improve everyday communication (Ramsberger, 2005). The underlying factor structure of nonverbal tasks has been well studied in healthy individuals (e.g., Leonberger, Nicks, Larrabee, & Goldfader, 1992;Tulsky & Price, 2003), but to a lesser extent in special clinical populations (Jones, van Schaik, & Witts, 2006;Ryan & Paolo, 2001;van der Heijden & Donders, 2003). Tulsky and Price (2003) showed that the nonverbal Performance IQ measures from the Wechsler Adult Intelligence Scale-3rd Edition (WAIS-III; Wechsler, 1997a), including Matrix Reasoning, Block Design, Picture Completion, and to a lesser extent Picture Arrangement, load strongly on a perceptual/nonverbal factor.…”
Section: Unravelling Nonverbal Cognitive Performance In Acquired Aphasiamentioning
confidence: 99%
“…The third level contains 14 subtests that are scored from 1 to 20. We did not take into account the factor scales because their validity when the scores are low has been refuted in previous analyses (Jones et al. 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding tests of reasoning abilities, respective comparative studies in LSAs are still missing. However, there is evidence that for people with severe intellectual disabilities the factor structure of well-established intelligence batteries might break down (Jones et al, 2006; MacLean et al, 2011; for opposing results see Reynolds et al, 2013). This highlights that many cognitive measures that were originally developed for a general student population are either not comparable for students with SEN or, even worse, do not allow for a coherent construct measurement among students with SEN. More importantly, measurement invariance of many cognitive tests is rarely explicitly examined for test-takers with cognitive disabilities (see the review by Renner and Mickley, 2015).…”
Section: Introductionmentioning
confidence: 99%